Mexico : 2007 Article IV Consultation; Staff Report; Staff Supplement; and Public Information Notice on the Executive Board Discussion for Mexico. (IMF Staff Country Reports; Country Report ;, 2007)
This 2007 Article IV Consultation highlights that the economic expansion of Mexico has continued albeit slowed by developments in the United States. Despite some pickup in the second and third quarter, growth is projected to be close to 3 percent for 2007 as a whole. Fiscal policy is on track to achieve balance for 2007, on the traditional budget measure, as required by the new Fiscal Responsibility Law. Executive Directors have commended the improvements in macroeconomic and financial policies that have helped Mexico to reduce significantly external and internal vulnerabilities over the years.